The Use of Mind Mapping Model in Learning Argumentative Essay Writing - Saputra, Nanda; Setiyawan, Dwi; Sumarlam, Sumarlam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Students sometimes struggle with writing argumentative essay. To address this obstacle, this study attempts to include the Mind Mapping approach into the writing learning process. The objective of this study was to ascertain the procedure and outcome of argumentative essay writing. The writing process was elicited through interviews and open-ended questions; the writing results were elicited via a written exam. The approach employed is one of descriptive qualitative analysis. The results of post-test study indicate that students' comprehension of the generic structure of argumentative essays has considerably improved. That is, the Mind Mapping style of writing instruction can help students enhance their ability to write argumentative essays. Additionally, student responses indicate that they find it simpler to create argumentative and more focused essays using the Mind Mapping approach since it enables them to develop ideas more solidly and coherently.